Tribological behaviour of a self-lubricated GO/WC–12Co thermal spray coating. (3rd October 2018) - Tian, H.L.; Guo, M.Q.; Wang, C.L.; Tang, Z.H.; Cui, Y.J.
ABSTRACT: In this work, we report on the first thermal spray coatings to consist of graphene oxide (GO) embedded in a WC–12Co matrix. The purpose of these coatings is to release lubricant into the system when needed. These coatings were prepared using detonation gun spraying, and tribological tests of the coatings were performed. The results indicated that a coating containing embedded GO exhibited approximately half the wear rate and a 28% lower friction coefficient than a comparable coating without GO. These results were attributed to the presence of GO platelets adhering to the friction surface that formed a self-lubricating layer.